INFLUENZA AND ACUTE VIRAL RESPIRATORY INFECTIONS IN THE PRACTICE OF THE EMERGENCY CREWS OF MOSCOW - N. F. Plavunov; V. A. Kadyshev; T. Ya. Chernobrovkina; L. N. Proskurina; E. V. Kardonova (Архивъ внутренней медицины)
Influenza and acute viral respiratory infections have a great social significance during epidemic rise of morbidity and demand differential diagnosis of pneumonia with bacterial etiology and consultation with an infectious disease doctor in case of seeing patients in non-core hospitals. This article highlights the problem of influenza and acute respiratory viral infections’ early diagnosis. Clinical manifestations of influenza and other respiratory extremely similar. The differential diagnosis must take into account the presence of mixed infection in the same patient. According to the results of consultative infectious ambulance teams in 2014-2016, quality of diagnostics of this infectious pathology was examined. Observed deaths in persons later seeking medical treatment, not receiving timely antiviral therapy and related to high-risk groups: patients with obesity, chronic alcohol intoxication, diabetes, pregnant women. Influenza and acute viral respiratory infections, more complicated by pneumonia, people in the older age group, indicating the need for timely medical evacuation of patients older than 60 years. In some cases, in the diagnosis of influenza was helped by the results of laboratory studies (especially the trend to leukopenia) and a positive rapid test. It should be noted that a negative rapid test for influenza was not a reason for exclusion of the diagnosis “influenza”.